Management functions displayed by Prophet Muhammad in two major events - Berisha, Hajdin; Ismail, Yusof (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2018)
Prophet Muhammad (ṣal-Allāhu ʿalayhi wa sallam) above all was a man. Before receiving his revelation (wahy) he worked as a businessman, conducted and managed a lady entrepreneur’s business, and subsequently married the owner. By contemporary definition he was a manager of a business but was not referred to as such in the literature. After becoming a Messenger (Rasul), he planned, organized, led and controlled – referred to as four management functions in contemporary literature -- several important events related to the affairs of Muslims. The two major historical events in which he had displayed the four management functions were migration (Hijrah) and Battle of Badr. The primary aim of this study is to identify the extent to which Muhammad (ṣal-Allāhu ʿalayhi wa sallam) displayed the four contemporary management functions in these two events. The study uses content analysis approach to dissect and synthesize the qualitative data. It attempts to pair the activities of Muhammad (ṣal-Allāhu ʿalayhi wa sallam) based on Qur'an and Sunnah which have existed over 1400 years with typical management functions developed only recently. Results reveal that activities of Muhammad (ṣal-Allāhu ʿalayhi wa sallam) may be approximated with four contemporary management functions.